Pengelolaan Konten Dakwah Islam di Media TikTok Akun @irfanrizkihaas - Fatimatuzzahra; Kiki Zakiah Darmawan (UNISBA Press, 2024)
Abstract. TikTok is one of the applications used by da'i as a medium for da'wah. One of them is the @irfanrizkihaas account. The purpose of this study is to find out about how the management of Islamic da'wah content in TikTok media on the @irfanrizkihaas account. Management theory proposed by George R. Terry is used as a map for this research. Computer Mediated Communication (CMC) theory is used to explain data findings. Da’wah management includes (1) Planning, (2) Organizing, (3) Actuating, and (4) Controlling. Based on the results of the research discussion, it is concluded that the planning carried out is researching content or identifying trends through content and websites, monitoring performance for improvement, and creating content. Organizing that is done is looking for ideas together, editing using the CapCut application, and always motivating the team. Actuating is answering questions using video or in the form of comments. Meanwhile, controlling is done by evaluating the number of views, likes, comments, and saves which are classified as less than optimal. Abstrak. TikTok merupakan salah satu aplikasi yang dimanfaatkan oleh para da'i sebagai media dakwah. Salah satunya adalah akun @irfanrizkihaas. Tujuan penelitian ini adalah untuk mengetahui mengenai bagaimana pengelolaan konten dakwah Islam di media TikTok pada akun @irfanrizkihaas. Teori Manajemen yang dikemukakan oleh George R. Terry dipakai sebagai peta untuk penelitian ini. Teori Computer Mediated Communication (CMC) digunakan untuk menjelaskan temuan data. Pengelolaan dakwah meliputi (1) Planning (Perencanaan), (2) Organizing (Pengorganisasian), (3) Actuating (Pelaksanaan), dan (4) Controlling (Pengawasan). Berdasarkan hasil pembahasan penelitian disimpulkan bahwa planning yang dilakukan yaitu me-riset konten atau mengidentifikasi tren melalui konten dan website, memantau kinerja untuk perbaikan, dan membuat konten. Organizing yang dilakukan yaitu mencari ide bersama, mengedit menggunakan aplikasi CapCut, dan selalu memotivasi tim. Actuating yang dilakukan yaitu menjawab pertanyaan menggunakan video atau dalam bentuk komentar. Sedangkan controlling yang dilakukan yaitu mengevaluasi jumlah view, likes, comment, dan save yang tergolong kurang optimal.